Analisis Kemampuan Manajerial Kepala Sekolah dalam Meningkatkan Kinerja Guru Sekolah Dasar - Dhea Annisa Oktarizka; Leli Haimah (Universitas Jambi, 2023)
The principal is a functional teacher who carries out the mandate to become a leader in a school, which is carried out by the learning process or the connection between teachers and students in the implementation of learning. Managerial principals include planning, implementing, monitoring and evaluating. In improving teacher performance, managerial leadership skills are needed. The performance of a teacher greatly influences the quality of learning/education which has implications for the quality of educational output after finishing school. Teacher performance is the teacher's perception of teacher work performance related to work quality, responsibility, honesty, cooperation and initiative. improving teacher performance, namely, program personnel discussing to determine the program and steps that must be taken by involving teachers in various education and training, activating the MGMP forum, providing the necessary facilities and supervising, encouraging/directing. The efforts made by the principal of the school turned out to be effective. The purpose of this research is to describe the managerial abilities of school principals in improving the performance of elementary school teachers. By using a qualitative approach and descriptive research methods.